Policy Evaluation Using Causal Inference Methods - Denis Fougère; Nicolas Jacquemet (Institute of Labor Economics (IZA), 2020)
This chapter describes the main impact evaluation methods, both experimental and quasi-experimental, and the statistical model underlying them. Some of the most important methodological advances to have recently been put forward in this field of research are presented. We focus not only on the need to pay particular attention to the accuracy of the estimated effects, but also on the requirement to replicate assessments, carried out by experimentation or quasi-experimentation, in order to distinguish false positives from proven effects.
Keywords: C1; C2; C3; C54; 330; causal inference; evaluation methods; causal effects